Application of combinatorial-logical approach for managing team of multi-project organization - Доценко, Наталья Владимировна (Technology audit and production reserves, 2015)
The features of managing the project team of multi-project organization are considered. The literature analysis showed that the management of projects in the multi-project organization must take into account limitations related to the involvement of employees in several projects of the portfolio, the maximum allowable engagement metrics for each job position, the restrictions associated with the interests of stakeholders. It is proposed to use the criterion of the degree of involvement of human resources for the analysis of the project portfolio. It is proposed to use a positional diagram of overlapping projects by «human resources» parameter to analyze the involvement of human resources in the project portfolio. A method for the analysis of the involvement of human resources in the portfolio, based on the use of combinatorial-logical approach to managing teams of multi-project organization was developed. An example of applying the method of analysis of the staff involvement in the portfolio projects was considered.